IbM MEMBANGUN âDESA CERMATâ MELALUI BIMBINGAN BELAJAR DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Susanti, Vera Dewi; Maharani, Swasti (Jurnal Terapan Abdimas, 2016)
IbM is motivated by the many children who come from poor families who can not follow the lessons, after school activities so that they spend a lot of play. In addition , many students and graduates who do not have the activity / work due to lack of jobs. Therefore, in this IbM the researchers intend to make les. In this IbM focused guidance for poor children and will involve students and graduates IKIP PGRI Madiun. Partner is the chief village IbM Watuompak and Bangunrejo. IbM aims to improve student learning outcomes through tutoring mathematics as a means to build a